Total Nutrient Uptake by Grain plus Straw and Economic of Fertilizer Use - Kabir, MH; Talukder, NM; Uddin, MJ; Mahmud, H; Biswas, BK (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted at BINA (Bangladesh Institute of Nuclear Agriculture) substation, Satkhira on slightly calcareous silty clay soil during the boro season of 2009-2010 to investigate the effects of different combinations of inorganic fertilizers in order to achieve sustainable high yield goal in the STL-655 rice mutant cultivar. The six treatment combinations were: T1 (absolute control), T2 (N60 P20 K40 S10 Zn1), T3 (N80 P25 K50 S15 Zn1.5), T4 (N100 P30 K60 S20 Zn2), T5 (N120 P35 K70 S25 Zn3) and T6 (N140 P40 K80 S30 Zn4) that was laid out in a randomized complete block design (RCBD) with three replications having per plot size was 5m x 4m. The results revealed that grain and straw yields of STL-655 rice mutant responded significantly with the different treatment combinations. The highest grain (3.95 t/ha) and straw yield (7.38 t/ha) was obtained in T6 (Soil test basis high yield goal) treatment, which was significantly higher than all other treatments. The treatment T6 (N140 P40 K80 S30 Zn4) caused an increase of 60% grain yield and 27% higher straw yield over the control. Nutrient uptake of N, P, K and S by grain of boro rice (STL-655 rice mutant) varied from 25.14 to 48.02, 5.40 to 8.14, 11.76 to 23.02 and 4.15 to 7.09 kg/ha, respectively. The N, P, K and S uptake by straw of boro rice (STL-655 rice mutant) varied from 20.36 to 35.85, 5.47 to 11.05, 59.01 to 159.6 and 9.54 to 12.97 kg/ha, respectively. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10139 J. Environ. Sci. & Natural Resources, 4(2): 83-87, 2011